2021
DOI: 10.3389/fpsyt.2021.637863
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and GABA Homeostasis and Neurometabolism in Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a leading cause of distress, disability, and suicides. As per the latest WHO report, MDD affects more than 260 million people worldwide. Despite decades of research, the underlying etiology of depression is not fully understood. Glutamate and γ-aminobutyric acid (GABA) are the major excitatory and inhibitory neurotransmitters, respectively, in the matured central nervous system. Imbalance in the levels of these neurotransmitters has been implicated in different neurological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 187 publications
(235 reference statements)
2
69
0
Order By: Relevance
“…However, among other things, research has revealed the relationships between amino acids homeostasis, neurotransmission, and lithium administration [15,22,23]. This is consistent with the fact that, according to some authors, the neurotransmission systems play an important role in the course of affective disorders [24,25].…”
Section: Introductionsupporting
confidence: 69%
“…However, among other things, research has revealed the relationships between amino acids homeostasis, neurotransmission, and lithium administration [15,22,23]. This is consistent with the fact that, according to some authors, the neurotransmission systems play an important role in the course of affective disorders [24,25].…”
Section: Introductionsupporting
confidence: 69%
“…Reduction in BDNF and GABA neurotransmission co-occur in the mPFC tissues and has been repeatedly seen in animal models and human subjects, and this has been associated with anhedonia and anxiety [ 54 , 79 – 82 ]. In addition, treatment with antidepressants and anti-anxiety agents, as well as repetitive transcranial magnetic stimulation treatment has been shown to enhance GABA and BDNF expression in depression [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing literature supports the notion that a widespread network dysconnectivity, as opposed to aberrant responses within select brain regions, is what characterizes and possibly drives pathophysiological changes associated with MDD ( 35 , 38 ). Behind these changes, a variety of molecular processes related to glutamate cycling and release may be implicated, including the decreased expression NMDA-Rs ( 39 41 ), AMPA-Rs ( 41 , 42 ), or mGluRs ( 43 ), which have been reported both in humans and animal models of depression, as well as in postmortem brains of suicide victims ( 39 , 44 ).…”
Section: Glutamatergic Neurocircuitry Dysfunction In Major Depressive...mentioning
confidence: 98%
“…For the purposes of this review, we define cortical pathways as those with at least one node situated in the cerebral cortex, and subcorticolimbic pathways as those with no nodes in the cerebral cortex. The cortical glutamatergic pathways can be further subdivided into five major arcs ( 35 , 36 ), illustrated in Figure 1 . Similarly, the subcorticolimbic glutamatergic pathways can be categorized into hippocampal and amygdalar, where HPC and AMYG are the central limbic nodes ( 37 ), illustrated in Figure 2 .…”
Section: Overview Of Glutamatergic Neurocircuitrymentioning
confidence: 99%
See 1 more Smart Citation